2011
DOI: 10.1108/00251741111094437
|View full text |Cite
|
Sign up to set email alerts
|

Innovation or imitation? The role of organizational culture

Abstract: Purpose -Innovation is crucial for attaining a competitive advantage for companies. Innovation, versus imitation, motivates companies to launch new products and become pioneers on markets. Many factors have been shown to be determinants for supporting an organizational innovative orientation. One of them is organizational culture. The objective of this paper is to analyze the organizational culture that fosters or inhibits organizational innovation and imitation strategy. Design/methodology/approach -The paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
253
2
20

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 435 publications
(291 citation statements)
references
References 106 publications
(138 reference statements)
16
253
2
20
Order By: Relevance
“…Although it has been shown that the organizational culture plays an important role in the way firms innovate (Ç akar and Ertürk 2010;Naranjo-Valencia et al 2011), there is still little research on the relationship between organizational culture and the different types of innovation in the family firm context. Previous research has shown that organizational culture is responsible for the innovativeness of a family firm (e.g., Naranjo-Valencia et al 2011), the management style of its leaders (e.g., Leenen 2005) as well as a less formal and more de-centralized structure (e.g., Craig and Moores 2006). In short, if a family firm wants to grow, be innovative and entrepreneurial, it should (constantly) question itself about whether the culture within the firm as well as the applied leadership style of the entrepreneur is also entrepreneurial (e.g., Blumentritt et al 2005), and if its organizational structure still fits the requirements of a rapidly changing environment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it has been shown that the organizational culture plays an important role in the way firms innovate (Ç akar and Ertürk 2010;Naranjo-Valencia et al 2011), there is still little research on the relationship between organizational culture and the different types of innovation in the family firm context. Previous research has shown that organizational culture is responsible for the innovativeness of a family firm (e.g., Naranjo-Valencia et al 2011), the management style of its leaders (e.g., Leenen 2005) as well as a less formal and more de-centralized structure (e.g., Craig and Moores 2006). In short, if a family firm wants to grow, be innovative and entrepreneurial, it should (constantly) question itself about whether the culture within the firm as well as the applied leadership style of the entrepreneur is also entrepreneurial (e.g., Blumentritt et al 2005), and if its organizational structure still fits the requirements of a rapidly changing environment.…”
Section: Resultsmentioning
confidence: 99%
“…It would be especially interesting to understand in greater detail how the organizational culture plays a role in the innovation processes of family firms. Although it has been shown that the organizational culture plays an important role in the way firms innovate (Ç akar and Ertürk 2010;Naranjo-Valencia et al 2011), there is still little research on the relationship between organizational culture and the different types of innovation in the family firm context. Previous research has shown that organizational culture is responsible for the innovativeness of a family firm (e.g., Naranjo-Valencia et al 2011), the management style of its leaders (e.g., Leenen 2005) as well as a less formal and more de-centralized structure (e.g., Craig and Moores 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prowadzi to do konkluzji, że kluczową kompetencją organizacji wzmacniającej swoją innowacyjność jest klimat innowacyjny, stwarzający warunki, w których pracownicy chcą i angażują się w takie działania [Burke, Litwin, 1992;Woodman, Sawyer, Griffin, 1993;Ekvall, 1996;Naranjo-Valencia et al, 2011;Wolf, Kaudela-Baum, Meissner, 2012]. Innowacje tworzone są przez ludzi, a proces ich tworzenia jest uwarunkowany interakcjami i procesami społecznymi zachodzącymi w zespołach pracowniczych [Agrell, Gustafson, 1996;Van Offenbeek, Koopman, 1996;Drach-Zahavy, Somech, 2013].…”
Section: Dyskusjaunclassified
“…It is often the best way to explain inimitable firm actions such as innovation and adaptivity that frustrate traditional approaches that assume a central tendencies and known distributions (Naranjo-Valencia et al, 2011). Why is culture a deeper element of firms?…”
Section: Firm Culture In Contextmentioning
confidence: 99%